EIT-based quantum memory for single photons from cavity-QED - Himsworth, M; Nisbet, P; Dilley, J; Langfahl-Klabes, G; Kuhn, A (Springer-Verlag, 2011)
We investigate the feasibility of implementing an elementary building block for quantum information processing. The combination of a deterministic single photon source based on vacuum stimulated Raman adiabatic passage (V-STIRAP), and a quantum memory based on electromagnetically induced transparency (EIT) in atomic vapour is outlined. Both systems are able to produce and process temporally shaped wavepackets which provide a way to maintain the indistinguishability of the photons. We also propose an efficient and robust 'repeat-until-success' quantum computation scheme based on this hybrid architecture. © 2011 Springer-Verlag.